Physical Modeling for Virtual Manufacturing Systems and Processes - Jan C. Aurich; Bahram Ravani; Achim Ebert; Bernd Hamann; Ralf Müller; Tarek Zohdi; Benjamin Kirsch (Trans Tech Publications Ltd, 2017)
International Research Training Group (IRTG) 2057Selected, peer reviewed papers from the 1st Conference on Physical Modeling for Virtual Manufacturing Systems and Processes, June 8-9, 2017, Speyer, Germany